Determination of Antimony in Zahedan Drinking Water - ATASHI, HOSSEIN; SAHEBI SHAHEMABADI, MEHDI; SALEK, SAMI (Asian Journal of Chemistry, 2010)
This article explains the status of antimony in Zahedan aquifer that lies in south east of Iran. We have measured the antimony concentration of 10 wells randomly by flame atomic absorption spectroscopy method. The minimum and maximum concentration of this element was 5.41 and 6.04 ppb in these samples, respectively. These amounts were much more than the standard limit (0.005 ppm). Isoconcentration contours were drawning on geological map of the area to determine the origins of antimony contamination. We have defined the origin of ground water pollution by obtaining information about industrial, agricultural and animal husbandry activities and geology and geochemistry of the region.